EVOLUTIONARY RELATIONSHIP AND REPURPOSING OF SARS INHIBITORS AGAINST SURFACE GLYCOPROTEIN OF SARS-COV-2 - RAJBHAR, PRIYANKA; SINGH, DIKSHANT; FATIMA, RUKHSAR; YADAV, RUCHI (International Journal of Applied Pharmaceutics, 2021)
Objective: Coronaviruses are a group of similar viruses which cause fatal infection and responsible for affecting the upper respiratory tract in many organisms. Throughout the time these viruses have been found to affect human life by causing major pandemics like SARS, MERS and COVID-19 due to their high rate of mutation and zoonotic transmission. Repurposing of a drug could be a solution for this challenge, as many previously available drugs hold great potential to act as a drug molecule. Interfering this interaction could be a potent mechanism to stop the viral infection and propagation. Methods: In the current study we have predicted the evolutionary relationship of nCoV using three viral proteins Nucleocapsid phosphoprotein, membrane glycoprotein and Envelop protein with accession number YP_009724397, YP_009724393 and YP_009724392 respectively. Phylogenetic tree was constructed and evaluated using the bootstrap method. Homology modeling and docking studies has been done to identify the interaction and binding affinity of SARS drugs. Results: Phylogenetic tree shows that Nucleocapsid phosphoprotein is originated from Hypsugo Bat Coronavirus, Membrane glycoprotein is originated from MERS Corona Virus and Envelop proteins have originated from Ferret coronavirus. From the docking result we concluded that Precose (glide score-8.372) shows that it has stable and strong interaction with Spike glycoprotein. Conclusion: Precose which is commonly known as Acarbose can act as a potential inhibitor for the spike glycoprotein. This paper described and highlighted the importance of repurposing of the previously available drug to act as a potent inhibitor in the newly discovered or novel diseases.